2016
DOI: 10.1016/j.scitotenv.2016.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Is digestate safe? A study on its ecotoxicity and environmental risk on a pig manure

Abstract: Abstract. Digestate represents a precious by-product in particular in agriculture, however its impact on the environment and human health is still unexplored. In this work, the toxicity of a pig slurry digestate was assessed through 7 ecotoxicity tests and considering 10 different endpoints. Besides, a synthetic index was applied to the outputs of the battery of tests for the environmental risk assessment, in order to evaluate the opportunity to use directly this kind of digestate in agriculture or to introduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(51 citation statements)
references
References 37 publications
2
40
1
8
Order By: Relevance
“…It has recently been characterized from a chemical and ecotoxicological point of view (Tigini et al, 2016 Chlorella vulgaris CCAP 211/11b (Culture Collection of Algae and Protozoa, Argyll, UK) was selected for this study in view of our previous experiences with digestates (Franchino et al, 2013). Firstly, C. vulgaris was pre-grown in 250 mL Erlenmeyer flasks containing 100 mL of Removal efficiency (RE) was estimated by dividing the difference between the initial nutrient concentration and that on day n (Ci-Cn) by Ci, and then multiplied by 100, while the Elimination Capacity (EC) by dividing the difference between the nutrient concentration of two subsequent samples (Cn-1 and Cn) by the time elapsed between them.…”
Section: Microalgae Growth and Nutrient Removal In Diluted Digestatementioning
confidence: 99%
See 2 more Smart Citations
“…It has recently been characterized from a chemical and ecotoxicological point of view (Tigini et al, 2016 Chlorella vulgaris CCAP 211/11b (Culture Collection of Algae and Protozoa, Argyll, UK) was selected for this study in view of our previous experiences with digestates (Franchino et al, 2013). Firstly, C. vulgaris was pre-grown in 250 mL Erlenmeyer flasks containing 100 mL of Removal efficiency (RE) was estimated by dividing the difference between the initial nutrient concentration and that on day n (Ci-Cn) by Ci, and then multiplied by 100, while the Elimination Capacity (EC) by dividing the difference between the nutrient concentration of two subsequent samples (Cn-1 and Cn) by the time elapsed between them.…”
Section: Microalgae Growth and Nutrient Removal In Diluted Digestatementioning
confidence: 99%
“…However, particularly high ammonia concentration like that found in pig manure remains a major challenge because it is often responsible for microalgal growth inhibition (Tigini et al, 2016). Moreover, it can pose a serious environmental issue as in Europe pig farming is a major agricultural industry and many large centralised pig farms have been established.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such results are in accordance with those reported by other authors ( Alburquerque et al, ; Pivato et al, ; Stefaniuk et al, ; Tigini et al, ), who also observed that as a general trend, the application of low concentrations of AD acted as a stimulant giving higher values of GI and stimulating seedling growth. Such an improvement in germination could be related not only to the nutrients provided by the digestate solutions, but also to a phytohormone‐like effect ( Emino and Warman , ; Moldes et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Research focused on the effects of digestate on soil microbial community structure and activity also proved that direct application of digestate on soil (in contrast to compost or manure) did not stimulate microbial activity with exception of nitrification (Gomez-Brandon et al 2016). The toxicity of digestate to bacteria was also proved in the comparative study of seven ecotoxicity tests (Tigini et al 2016), where bioassay with Vibrio fisheri was the most sensitive bioassay. This recent study as probably the first scientific paper in this field clearly concludes, that the digestate represents extremely high environmental risk and that is why a pre-treatment of digestate is needed to reduce toxicity and negative environmental impact.…”
Section: : Effect Of Fugate and Digestate On Photosynthetic Activitymentioning
confidence: 95%